The effect of high-fat diet on the pharmacokinetics of ondansetron hydrochloride tablets in healthy Chinese subjects - Zhao, Na; Jia, Caiyun; Hu, Yiting; Sun, Xue; Song, Haojing; Qiu, Bo; Bai, Wanjun; Dong, Zhanjun (Frontiers in Pharmacology, 2025)
BackgroundThis study aimed to assess how a high-fat diet impacts the pharmacokinetics and safety characteristics of 8 mg Ondansetron hydrochloride tablets among healthy Chinese individuals.Subjects and methodsThe findings presented here were obtained from a bioequivalence study, in which individuals were randomly assigned to consume Ondansetron hydrochloride tablets either following a meal or subsequent to a high-fat diet containing 978.6 kcal, with 54.6% of the calories derived from fat. The plasma concentrations of Ondansetron were measured through the utilization of high-performance liquid chromatography-mass spectrometry (LC-MS/MS) after collecting blood samples. For the computation of pharmacokinetic parameters, the non-compartmental module from Phoenix WinNonlin Version 8.2 was utilized Additionally, the BE module within WinNonLin was utilized to statistically analyze key pharmacokinetic metrics, including the maximum level of concentration (Cmax), the area beneath the concentration-time curve spanning from zero to the final quantifiable time point (AUC0-t), and the area beneath the concentration-time curve extending from zero to a theoretical limitless point (AUC0–∞) in plasma. A total of 53 healthy subjects participated in the study and were divided into a fasted cohort and a postprandial cohort.ResultsOndansetron had lower Cmax, AUC0–t, and AUC0–∞in plasma when taken with food compared to when taken on an empty stomach, with the 90% confidence interval falling outside the acceptable range of 80.00%–125.00%.The occurrence of treatment-related side effects was comparable in both the fasted and postprandial groups, as was the incidence of adverse drug reactions.ConclusionThe study concluded that the high-fat meal had a notable impact on how Ondansetron is processed in the body. Healthy subjects tolerated all treatments well and safely under both postprandial and fasted conditions.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/index.html, identifier CTR20213116.